2005
DOI: 10.1074/jbc.m510802200
|View full text |Cite
|
Sign up to set email alerts
|

The Human Enhancer Blocker CTC-binding Factor Interacts with the Transcription Factor Kaiso

Abstract: CTC-binding factor (CTCF) is a DNA-binding protein of verte-brates that plays essential roles in regulating genome activity through its capacity to act as an enhancer blocker. We performed a yeast two-hybrid screen to identify protein partners of CTCF that could regulate its activity. Using full-length CTCF as bait we recovered Kaiso, a POZ-zinc finger transcription factor, as a specific binding partner. The interaction occurs through a C-terminal region of CTCF and the POZ domain of Kaiso. CTCF and Kaiso are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 45 publications
5
49
0
Order By: Relevance
“…Radiolabeled ZBTB4 was produced by in vitro transcription and translation of plasmid pSG5-ZBTB4 using rabbit reticulocyte lysate (TNT, Promega, Madison, WI, USA). The pulldown was then performed as described earlier (Defossez et al, 2005).…”
Section: Two-hybrid Screeningmentioning
confidence: 99%
“…Radiolabeled ZBTB4 was produced by in vitro transcription and translation of plasmid pSG5-ZBTB4 using rabbit reticulocyte lysate (TNT, Promega, Madison, WI, USA). The pulldown was then performed as described earlier (Defossez et al, 2005).…”
Section: Two-hybrid Screeningmentioning
confidence: 99%
“…Co-association events such as those with the histone deacetylase SIN3 [54], the thyroid hormone receptor [55], nucleophosmin [56], Kaiso [57] and the DEAD-box RNA helicase p68 with associated non-coding RNA [58] have been implicated in its insulator function. Interestingly, the p68 RNA -protein complex appears required for positioning cohesin at the CTCF sites of the H19-Igf2 ICR [58].…”
Section: Ctcf and Other Binding Partnersmentioning
confidence: 99%
“…10 A significant amount of data indicates that BTB domains are involved in the recruitment of non-BTB-containing regulator proteins. [11][12][13] Another set of experiments have shown that BTB domains of different proteins in some cases can specifically interact with each other, but it is unknown how such interactions proceed. Rarely, heterodimerization of two different BTBs has been observed.…”
Section: Introductionmentioning
confidence: 99%